2000
DOI: 10.1590/s0041-87812000000500002
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocyst(e)inemia in chronic stable renal transplant patients

Abstract: RHCFAP/3019 MACHADO DJ de B et al. -Hyperhomocyst(e) Purpose:Hyperhomocyst(e)inaemia is an important risk factor for atherosclerosis, which is currently a major cause of death in renal transplant patients. The aim of this study was to assess the influence of immunosuppressive therapy on homocyst(e)inemia in renal transplant recipients.Methods: Total serum homocysteine (by high performance liquid chromatography), creatinine, lipid profile, folic acid (by radioimmunoassay-RIA) and vitamin B12 (by RIA) concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
2
2
0
Order By: Relevance
“…So far, it can be concluded that the diabetogenic effect of tacrolimus is not of great concern, and it can be managed by reducing the dose of tacrolimus, early corticosteroid withdrawal and avoiding it in hepatits C patients 18 . Hyperhomocysteinaemia was not seen under the use of tacrolimus compared to cycloprin, as previously reported 19,20 . The lower serum creatinine levels at the third month observed in patients receiving tacrolimus compared to cyclosporin with the same doses of azathioprine, MMF and prednisone, suggest that tacrolimus is a better imunossupressor to prevent subclinial acute rejection and is also less nephrotoxic 21,22 .…”
Section: Figure III -Frequency Of Patients Presenting Hypertension and Posttransplant Diabetes Mellitussupporting
confidence: 80%
“…So far, it can be concluded that the diabetogenic effect of tacrolimus is not of great concern, and it can be managed by reducing the dose of tacrolimus, early corticosteroid withdrawal and avoiding it in hepatits C patients 18 . Hyperhomocysteinaemia was not seen under the use of tacrolimus compared to cycloprin, as previously reported 19,20 . The lower serum creatinine levels at the third month observed in patients receiving tacrolimus compared to cyclosporin with the same doses of azathioprine, MMF and prednisone, suggest that tacrolimus is a better imunossupressor to prevent subclinial acute rejection and is also less nephrotoxic 21,22 .…”
Section: Figure III -Frequency Of Patients Presenting Hypertension and Posttransplant Diabetes Mellitussupporting
confidence: 80%
“…Furthermore, we recently demonstrated in a prospective placebo‐controlled study using rats that plasma homocysteine concentration was not significantly elevated in CyA‐treated rats 93 . Our finding, coupled with those of others, 27,28 , 71,91 , 92 strongly suggests that CyA is unlikely to cause the hyperhomocysteinaemia seen in RTR. Therefore, mechanisms explaining the hyperhomocysteinaemia in RTR appear to be the same as those affecting ESRF patients; namely, reduced renal homocysteine metabolism and, possibly, the uraemic environment.…”
Section: Hyperhomocysteinaemia In Rtrsupporting
confidence: 67%
“…These suggestions have been refuted by studies showing plasma cysteine, a product of transsulphuration, was not significantly different in CyA‐treated RTR compared with non‐CyA‐treated RTR 25 and plasma homocysteine and red cell folate concentrations are correlated in CyA‐treated RTR 27,28,91 . In addition, plasma homocysteine concentrations in RTR treated with CyA were either 23% lower 92 or not significantly different 27,28,71 compared with concentrations in those RTR not receiving CyA, whereas serum creatinine was the strongest independent determinant of plasma homocysteine concentration in 86 stable RTR and CyA had no influence at all 71 . Differences in methodologies between the studies may account for the contrasting results, with some studies 27,28,71 adjusting for renal function and other determinants of hyperhomocysteinaemia whereas others 25,26 did not.…”
Section: Hyperhomocysteinaemia In Rtrmentioning
confidence: 99%
“…No significant correlation between the tHcy level and the doses of cyclosporine, prednisolone, and azathioprine was found in our study or in many other studies. [25][26][27] Others reported a significant positive correlation between the levels of serum Hcy and cyclosporine [28] but a lowering effect of mycophenolic acid on total plasma Hcy. [29] Multivariate regression analysis revealed that, besides creatinine clearance, only BW was a significant determinant of elevated total Hcy level in our renal transplant recipients.…”
Section: Discussionmentioning
confidence: 99%